North Atlantic multi-decadal variability - mechanisms and predictability - Keenlyside, Noel; Ba, Jin; Mecking, Jennifer V.; Omrani, Nour-Eddine; Latif, Mojib; Zhang, Rong; Msadek, Rym (World Scientific Publishing, 2016)
The North Atlantic Ocean undergoes pronounced basin-wide, multi-decadal variations. The corresponding fluctuations in sea surface temperature (SST) have become known as the Atlantic Multi-decadal Oscillation (AMO) or Atlantic multi-decadal variability (AMV). AMV is receiving increasing attention for three key reasons: (1) it has been linked to climate impacts of major socioeconomic importance, such as Sahel rainfall; (2) it may temporarily mask anthropogenic global warming not only in the North Atlantic Sector, but over the Northern Hemisphere (NH); and (3) it appears to be predictable on decadal timescales. This chapter provides an overview of current understanding of AMV, summarizing proposed mechanisms, our ability to simulate and predict it, as well as challenges for future research. acceptedVersion